Brand Ambassadors Moderate Product Quality Brand Image And Consumer Purchasing Decisions: Duta Merek Memoderasi Kualitas Produk Citra Merek Dan Keputusan Pembelian Konsumen - Fitria Firdiani; Dina Arumalaita; Sigit Hermawan (International Consortium of Education and Culture Research Studies, 2024)
General Background The beauty industry in Indonesia experiences intense competition driven by high consumer demand for skincare items. Specific Background To build consumer trust and secure market share, cosmetic manufacturers like Scarlett utilize strong corporate reputation and high standard product characteristics alongside celebrity endorsements. Knowledge Gap Despite the prevalence of celebrity endorsements, previous empirical research rarely examines their specific role as a moderating variable interacting with physical item characteristics and corporate reputation. Aims This study investigates how product quality and brand image determine purchasing decisions for Scarlett products, specifically analyzing the moderating role of brand ambassadors among university students. Results Quantitative analysis reveals that both product quality and brand image positively and significantly determine consumer purchasing choices. Furthermore, the presence of a brand ambassador significantly moderates and strengthens the relationship between physical product characteristics, corporate reputation, and final buying choices. Novelty This research introduces a novel framework by positioning celebrity endorsers not merely as direct drivers of sales, but as critical moderating catalysts that amplify the effects of underlying product and brand attributes. Implications Cosmetic producers must optimize physical item standards and maintain a positive corporate reputation while strategically deploying celebrity endorsers to maximize market acquisition and consumer buying choices. Highlights: • Physical item characteristics significantly drive buyer choices. • Positive corporate reputation directly stimulates skincare acquisitions. • Celebrity endorsers successfully amplify core marketing attributes. Keywords: Product Quality, Brand Image, Brand Ambassador, Purchasing Decisions, Moderating Variable